A systematic review of Bring Your Own Device (BYOD) authentication technique - Jamal, Fara; Abdullah@Selimun, Mohd. Taufik; Abdullah, Azizol; Mohd. Hanapi, Zurina (IOP Publishing, 2020)
This article provides a systematic review of Bring Your Own Device (BYOD) authentication technique. The review main goal is to identify the existing BYOD authentication technique and to categorize the technique according to BYOD security threat as well as to analyze the technique limitation. The review result shows that there are 25 authentication techniques proposed across both industry and academic areas to fit into BYOD implementation to enhance the security in preventing and detecting data leakage in the organization. It is hoped that the proposed BYOD authentication solution can help organizations to minimize the number of cases in data leakage while allowing the BYOD concept.